Normal Pressure Hydrocephalus as Cause of Urinary Incontinence – A Shunt for Incontinence - Rendtorff, R.; Novak, A.; Tunn, R. (Geburtshilfe und Frauenheilkunde, 2012)
Normal pressure hydrocephalus is a frequently missed clinical entity with the typical symptom triad of gait disturbance, urinary incontinence and dementia (Hakimʼs triad) and occurs mostly from the 6th decade of life onwards. Early therapy can lead to a complete reversal of the symptoms. The present case report is intended to draw attention to the clinical entity normal pressure hydrocephalus (NPH) since the afflicted patients often primarily consult a gynaecologist on account of the urinary bladder disorders.
Keywords: urinary incontinence; gynaecology; post-menopause